Caesarean section between doctrine to heresis. Medicoethical and deontological view of caesarology: an opinion - Dubravko Habek; Matija Prka; Anto Čartolovni; Anis Cerovac; Domagoj Dokozić (IMR Press, 2021)
Increasing the incidence of caesarean section is not in line with professional and deontological guidelines. Elective cesarean section prevents primordial prevention of chronic cardiovascular, gastrointestinal, imunological, endocrinological morbidity by peripartal programming. Elective non-medical indicated caesarean section is not a procedure that respects deontological, clinical etics, scientific and professional principles. It is like an unacceptable surgery outside the scope of medical ethics. Clientelism in high-risk clinical obstetric medicine is not a professional and deontologically correct category: a physician should not be a provider on request of healthy pregnant women with the potential to have a medically incorrect procedure and complications associated with it and to put a healthy pregnant/maternity and child status in the patient's status. The financial, social, political and cultural components must not outweigh good clinical practice and the moral principles of medicine.